BISNIS MODEL PADA PT. PLN (PERSERO) P3B JAWA BALI - Wibowo, Kuncoro (Journal of Information System, Applied, Management, Accounting and Research, 2025)
PLN Transmission as one of the most important business units in electricity must make changes in response to its macro environment. Although PT PLN is a monopoly company, the public response to its performance greatly affects the image of the company as a whole. The existing condition for the generating unit has been handed over to the private sector through Independent Plant Power (IPP). However, the transmission unit, which is the mediator between the generation and distribution units, needs to improve its capabilities through a shift from product oriented to market oriented. Despite the fact that this shift is difficult to do radically, this shift is done incrementally. The existing conditions for the back office still have many areas of improvement, especially for key resources, key activities and key partners. Furthermore, for the cost structure, the focus of improvement is to control fixed costs, considering that PLN is a capital-intensive company that is burdened by large depreciation costs. Based on the 9 foundations of the business model canvas analysis, it is recommended to renovate the value prepotition from Performance-to-Performance SIAP 99. With the recommended new value, improvements need to be made in the back office.